Awareness Regarding Attention Deficit Hyperactivity Disorder Among Teachers of Selected Schools in Municipality of Rupandehi - Bhattarai, S; Bhusal, CK; Jaishi, AB (Journal of Psychiatrists' Association of Nepal, 2020)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) is a chronic condition that affects millions of children and often continues into adulthood which includes a combination of persistent problems such as difficulty sustaining attention, hyperactivity and impulsive behavior. The aim of the study was to find out teachers awareness regarding ADHD. Material And Method: Descriptive cross-sectional study was used to find out awareness regarding ADHD among 77 teachers. Three private school were selected using simple random sampling technique, among them seventy seven primary school teachers were selected as a study sample by using enumerative method. Data was collected by pretested self-administered semi-structured questionnaire and the collected data was analyzed by using descriptive and inferential statistics with Statistical Package for Social Sciences (SPSS) Software version 20. Results: Ninety three percent of respondents had awareness that attention deficit hyperactivity disorder (ADHD) vary from person to person, 59.74% of respondents knew child with ADHD has a lower intelligence quotient than normal children. Sixty one percent of respondents had awareness that prolonged emotional disturbances as a risk factor of ADHD, 59.74% of the respondents had awareness that can't sit for long period to pay attention as symptom of ADHD and 64.94% of the respondents had awareness regarding teachers are the effective person for training of ADHD. Majority of the respondents had low awareness (55.84%) regarding ADHD. There was statistically significant association between awareness level regarding attention deficit hyperactivity disorder and years of teaching experience (p=0.043). Conclusion: It is concluded that awareness regarding ADHD is inadequate among teachers. Respondents had low awareness regarding management and risk factors of ADHD. Hence concerned authority should focus on organizing awareness programme on ADHD to school teachers.